Survival results according to Oncotype Dx recurrence score in patients with hormone receptor positive HER-2 negative early-stage breast cancer: first multicenter Oncotype Dx recurrence score survival data of Turkey - Ünal, Çağlar; Özmen, Tolga; Ordu, Çetin; Pilanci, Kezban Nur; İlgün, Ahmet Serkan and Gökmen, Erhan and Almuradova, Elvina and Özdoğan, Mustafa and Güler, Nilüfer and Uras, Cihan and Kara, Halil and Demircan, Orhan and Işık, Selver and Alço, Gül and Saip, Pınar and Aydın, Esra and Duymaz, Tomris and Çelebi, Filiz and Yararbaş, Kanay and Soybir, Gursel and Ozmen, Vahit (Frontiers in Oncology, 2023)
Background The Oncotype Dx recurrence score (ODx-RS) guides the adjuvant chemotherapy decision-making process for patients with early-stage hormone receptor-positive, HER-2 receptor-negative breast cancer. This study aimed to evaluate survival and its correlation with ODx-RS in pT1-2, N0-N1mic patients treated with adjuvant therapy based on tumor board decisions. Patients and methods Estrogen-positive HER-2 negative early-stage breast cancer patients (pT1-2 N0, N1mic) with known ODx-RS, operated on between 2010 and 2014, were included in this study. The primary aim was to evaluate 5-year disease-free survival (DFS) rates according to ODX-RS. Results A total of 203 eligible patients were included in the study, with a median age of 48 (range 26-75) and median follow-up of 84 (range 23-138) months. ROC curve analysis for all patients revealed a recurrence cut-off age of 45 years, prompting evaluation by grouping patients as ≤45 years vs. >45 years. No significant difference in five-year DFS rates was observed between the endocrine-only (ET) and chemo-endocrine (CE) groups. However, among the ET group, DFS was higher in patients over 45 years compared to those aged ≤45 years. When stratifying by ODx-RS as 0-17 and ≥18, DFS was significantly higher in the former group within the ET group. However, such differences were not seen in the CE group. In the ET group, an ODx-RS ≥18 and menopausal status were identified as independent factors affecting survival, with only an ODx-RS ≥18 impacting DFS in patients aged ≤45 years. The ROC curve analysis for this subgroup found the ODx-RS cut-off to be 18. Conclusion This first multicenter Oncotype Dx survival analysis in Turkey demonstrates the importance of Oncotype Dx recurrence score and age in determining treatment strategies for early-stage breast cancer patients. As a different aproach to the literature, our findings suggest that the addition of chemotherapy to endocrine therapy in young patients (≤45 years) with Oncotype Dx recurrence scores of ≥18 improves DFS.